2006
DOI: 10.1039/b609734k
|View full text |Cite
|
Sign up to set email alerts
|

First synthesis of 1,2,3-triazolo-linked (1,6)-α-d-oligomannoses (triazolomannoses) by iterative Cu(i)-catalyzed alkyne–azide cycloaddition

Abstract: The iterative copper(I)-catalyzed cycloaddition (rt or microwave) between an ethynyl alpha-C-mannoside and alkyl 6-azido-alpha-C-mannoside derivatives was suited to the (1,6)-ligation between alpha-D-mannose units through 1,4-disubstituted triazole bridges, thus resulting in the formation of linear oligomers (80-90% yield) with alternating triazole and mannose fragments up to a triazolo-pentamannose derivative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 46 publications
1
54
0
Order By: Relevance
“…To this end the pentamannoside 151 exhibiting a terminal ethynyl group was reacted with the azidefunctionalized oligomer 152 which was obtained by a simple manipulation of the triazole-linked pentamannoside that was earlier prepared in our laboratory. 85 The fidelity of the CuAAC was confirmed in this operation as well so that the decamannoside 153 was obtained in a rewarding isolated yield of 93%. The benzyl groups of 153 were removed to give compound 154 suitable for testing against Mbt cell wall biosynthesis (Fig.…”
Section: Synthesis Of Triazole-linked 16-a-d-oligomannosidesmentioning
confidence: 88%
See 1 more Smart Citation
“…To this end the pentamannoside 151 exhibiting a terminal ethynyl group was reacted with the azidefunctionalized oligomer 152 which was obtained by a simple manipulation of the triazole-linked pentamannoside that was earlier prepared in our laboratory. 85 The fidelity of the CuAAC was confirmed in this operation as well so that the decamannoside 153 was obtained in a rewarding isolated yield of 93%. The benzyl groups of 153 were removed to give compound 154 suitable for testing against Mbt cell wall biosynthesis (Fig.…”
Section: Synthesis Of Triazole-linked 16-a-d-oligomannosidesmentioning
confidence: 88%
“…84 We planned the preparation of mannose-triazole hybrids by a linear oligomerization strategy based on the construction of the triazole ring by iterative click CuAAC. After an initial exploratory work demonstrating the feasibility of our program, 85 we carried out the synthesis of the triazole-tethered oligomannosides shown in Fig. 8 in the following way 86 (Scheme 22).…”
Section: Synthesis Of Triazole-linked 16-a-d-oligomannosidesmentioning
confidence: 99%
“…Marra and co-workers [106] demonstrated that the iterative ''click'' reaction under CH (room temperature) or MW between an ethynyl α-C-mannoside and alkyl 6-azido α-C-mannoside derivatives was suitable for 1,6-ligation between α-d-mannose units through 1,4-disubstituted triazole bridges, resulting in the formation of linear oligomers (80-90% yield) with alternating triazole and mannose fragments up to a triazolopentamannose derivative. Comparison of CH and MWI conditions favored the latter, which dramatically reduced the reaction times, affording close or identical yields.…”
Section: Synthesis Of Heterocycles 997mentioning
confidence: 99%
“…For similar reasons we prepared the triazole-linked oligosaccharide triazolopentamannose [42] (Scheme 9). In fact, the glycopolymers were synthesized to promote nucleic acid delivery into cells in the presence of serum.…”
Section: Glycopolymers With Triazole Rings In the Chainmentioning
confidence: 99%
“…[44] The method was first applied to designed alkyne-modified oligodeoxyribonucleotides, which were subjected to multiple coupling with suitable azide-bearing labels such as glucose, cou-Scheme 8. Triazole-containing glycopolymer [41] (top) and oligosaccharide [42] (bottom) constructed by the A C H T U N G T R E N N U N G iterative CAAC process. [40] Scheme 9.…”
Section: Labeling Of Dna Strandsmentioning
confidence: 99%